Knowledge and attitude on halal food and Islamic eating practices among students of a public university in Malaysia - Abdul Latif, Mariam (2018)
The preservation of future generation and the protection of consumer welfare is a priority in view of the incremental negative behaviours existing in today’s societies at large. This qualitative and quantitative research on Knowledge, Attitude and Practices on Halal Food and Islamic Eating Practices among Students of Universiti Malaysia Sabah focused on halal food consumed by the Prophet Muhammad s.a.w. and his eating practices. The study covered 414 respondents through a convenience sampling by using a questionnaire on level of knowledge, attitude and practices and the food dietary recall. The data was analyzed by using SPSS version 25. This study highlighted that families play a big role in educating their family members on halal food as the study found that family is the main reference for source of information on halal food products followed with the internet and lecturers. The same findings are found in the religious and race perspective. All faculties at UMS has high level of knowledge about the concept of Halal and Haram in halal food, followed with Islamic law on halal food and beverages. This is maybe due to courses on halal and haram foods being offered at various faculties in UMS. This study also showed that although the majority of respondents has high level of knowledge on halal food but the practices of respondents consuming the sunnah food is low. This happens because the fruits such as dates, pomegranates and figs are quite expensive and not easily accessible in the city of Kota Kinabalu. The study also found that the Muslim respondents have positive attitude towards halal food and eating practices whereby they will always choose halal and tayyib food whenever they want to eat and they will eat in a congregation (with friends or family) when they want to eat. The study also showed that although Muslim students have a high level of knowledge about halal food, but this is not interpreted and applied in their daily lives. The respondents have satisfactory level on Islamic eating practices such as washing hands before and after eating, saying “Bismillah” before eating and sharing food with friends, but not because it is encouraged by Islam, but because it has become a custom or a part of their daily eating practices. This also happens because the Malaysian public is not familiar with eating food from Arab countries where it was a way of life for the Prophet s.a.w. This study also found that 94.7% of the respondents are in the ideal BMI category showing that respondents consumed the amount of energy as recommended. Results also showed that knowledge on Halal food was significantly correlated with attitude and practices of the UMS students showing positive linear correlations which confirms that better knowledge can lead to positive attitude and subsequently in good practices. The research also recommended the Halal Nutrition guideline through the food pyramid whereby it is actually relevant and befitting the halal nutrition but the whole regime has to be without the haram elements which are blood, pork, carrion and liquor to provide proper nutrition guidelines for quality and better consumption of halal food for the future generation.